AR replay in a small workspace - Yun Li; Kameda, Yoshinari; Ohta, Yuichi (2013 23rd International Conference on Artificial Reality and Telexistence (ICAT), 2013)
We propose "AR replay", a framework to record the working scene including a tutor's action in a small workspace, and then replay the tutor's action in front of a learner's view in an AR fashion (Figure.1). This framework uses one RGB-D camera for recording and replaying. On learning a task in a small workspace, when a tutor cannot be in the workspace, it is useful for a learner to check the action of the tutor by a video which was taken in advance in the same workspace. If the video can be replayed in an AR fashion, it will be more useful. We propose a new "AR replay" method by using one RGB-D camera. In our "AR replay", the action of tutor is aligned to the right place and the learner can check the action from various viewpoints. The action is shown as 3D dynamic shape with color and it is aligned to the workspace by the static geometric clues in the workspace. Since we expect the RGB-D camera is maneuvered to frame the interaction between the tutor and the static workspace environment, we assume the demand of changing viewpoint from the original recorded camera viewpoint is limited to some extent on checking the "AR replay". Our preliminary experimental system can acquire the 3D shapes about tutor's action and the workspace environment. Moreover, this system can produce the "AR replay" on a video see-through display, with which a learner can shift the viewpoint from the original path of the RGB-D camera in order to have the better view of the interaction between the tutor and the static workspace environment.